Structural, Solvent, and Temperature Effects on Protein Junction Conductance - Jonnalagadda, Gowtham Nirmal; Wu, Xiaojing; Hronek, Lukáš; Futera, Zdenek (The journal of physical chemistry letters, 2024)
Cytochrome b562 is a small redox-active heme protein that has served as an important model system for understanding biological electron transfer processes. Here, we present a comprehensive theoretical study of electron transport mechanisms in protein-metal junctions incorporating cytochrome b562 using a multi-scale computational approach. Employing molecular dynamics (MD) simulations, we generated junction geometries for both vacuum-dried and solvated conditions, with the protein covalently bound to gold contacts in various configurations. Coherent tunneling, described by the Landauer-Buttiker formalism within the density functional theory (DFT) framework, is compared to the incoherent hopping charge transport mechanism captured by the semi-classical Marcus theory. The tunneling was identified as the dominant mechanism explaining the experimental data measured on the cytochrome b562 junctions, exhibiting exponential yet very shallow distance dependence. While the structural orientations and protein contacts with the electrodes influence the junction conductance significantly, the solvation effects are relatively small, affecting the electronic properties mostly via the adsorption arrangement. On the other hand, the considerable temperature dependence of the conductance was found strong only for hopping, while the tunneling current magnitudes remain practically unaffected and are a good indicator of the coherent mechanism in this case.
Keywords: simulace molekulární dynamiky; cytochromy typu b; Gold; Electron Transport; Density Functional Theory; proteiny z Escherichia coli; Solvents; Molecular Dynamics Simulation; Temperature; zlato; Cytochrome b Group; rozpouštědla; teplota; transport elektronů; teorie funkcionálu hustoty; Escherichia coli Proteins